Bleaching Stained Arrested Caries Lesions: In vivo Clinical Study - Al-Angari, Sarah S.; AlHadlaq, Mashael; Abahussain, Noor; AlAzzam, Njood (European Journal of Dentistry, 2020)
Objective Conservative approaches to esthetically treat stained arrested caries lesions (s-ACLs) have not been explored in clinical studies. This study aims to investigate the efficacy of in-office dental bleaching agent, as a conservative approach, to esthetically treat s-ACLs.Materials and Methods Twelve patients (n = 46) presented with s-ACLs were treated with 40% hydrogen peroxide (in-office bleaching protocol; 20 minutes × 3). Color values were measured using a spectrophotometer (CIE L*a*b*), aided with digital photography to assess visual color change clinically. Measurements were taken for each specimen at baseline and immediately after bleaching.Statistical Analysis The color change calculated before and after bleaching for each dental substrate was analyzed using paired t-test (α = 0.05).Results The bleached s-ACLs had a significant increase in L* values (p < 0.001), and a significant decrease in both a* (p = 0.001) and b* (p = 0.007) values, indicating lighter color improvement (bleaching efficacy). The baseline mean of L*, a*, and b* values were 61.5, 2, and 15.4, respectively, and after bleaching were 67.7, 1.4, and 13.3, respectively, with a mean increase in ∆E of >7.9, which resulted in a visible clinical stain improvement as orange/light brown stains were removed completely, while gray/black stains improved to a lesser extent.Conclusion Significant color improvement was observed when the in-office bleaching protocol (40% hydrogen peroxide) was used in orange/brown s-ACLs. However, it showed lesser improvement in gray/black s-ACLs.
Keywords: arrested caries lesions; bleaching; color change; esthetics; hydrogen peroxide